FORMULATION OF FACE PACK POWDER USING SIMPLEX LATTICE DESIGN METHOD - Fitri, Aulia Kemala; Pratiwi, Liza; Nurbaeti, Siti Nani (Universitas Tanjungpura, 2024)
Face pack powder is a cosmetic preparation that has been developed in the pharmaceutical industry. In powder dosage formulations, the important components used are binders. This study aimed to obtain an optimal formulation of face pack powder with a combination of binders. The binders combined in this study were carbopol, hydroxypropyl methylcellulose (HPMC), and sodium carboxymethyl cellulose (CMC-Na). The binder combination in the formula was predicted with simplex lattice design (SLD) mehod of Design-Expert ® software. The applied method for making the face pack powder was wet granulation based on 13 runs of software with responses in the form of pH and moisture content. The results showed that the pH of the preparations was in the range of 5.2-6.3 and that the water content was 1.54-2.87%. The pH and water content data were then entered into the software to obtain the optimum composition with a carbopol : HPMC : CMC-Na ratio of 3:1:1. The optimum formulation of the face pack powder is with white color, smooth texture, vanilla scent, pH 5.4, and 1.64% moisture content. The optimum formula data was then analyzed using one-sample t-test to verify that the predicted formula and the experimental results do not differ significantly (p0.05) so that it could be used to design the optimum formula